Content of exogenous and endogenous brassinosteroids in bulbous crops of the genera Tulipa and Hyacinthus - Kalenchuk, Tatiana; Chernetskaya, Alla (Journal of the Belarusian State University. Ecology, 2025)
Bulbous plants occupy one of the leading positions among the vast diversity of herbaceous perennials. This group includes spring-flowering crops such as tulips and hyacinths. They are united by the presence of an underground storage organ – the bulb – and by the similarity of their life cycle, although they belong to different families: tulips are the brightest representatives of the Liliaceae L. family, while hyacinths belong to the Hyacinthaceae L. family. Phytohormones are the most important representatives of the endogenous regulatory system. Their distinctive feature is the ability to act in very small doses, serving as regulators of key physiological processes (cell division and growth, dormancy, stomatal regulation, etc.) [1]. The use of biologically active substances in floriculture allows for a fuller realization of the potential capabilities of plants by regulating such important processes as root formation and growth, stem and leaf development, transition to flowering, duration of flowering, as well as by reducing the damaging effects of adverse environmental factors. It has been established that treatment of various ornamental-flowering crops with concentrations of 0.00025% (epibrassinolide) and 0.000375% (homobrassinolide) per liter of aqueous solution results in a noticeable growth-promoting and adaptogenic effect, leading to extended flowering periods, improved product quality, and enhanced plant resistance to unfavorable conditions and diseases. It is also known that some synthetic analogs of brassinosteroids exhibit significant biological activity comparable to that of natural brassinosteroids [2]. These factors determine the scientific and practical interest in the synthesis and study of brassinosteroid derivatives, as well as in the development of convenient, highly sensitive, and rapid methods of their analysis. For the first time in Belarus, we studied the influence of brassinosteroids on the morphometric parameters of 22 tulip cultivars and 10 hyacinth cultivars. The article presents the results of enzyme immunoassay analysis of endogenous brassinosteroid content in the organs of plants of the genera Tulipa L. and Hyacinthus L. Determination of endogenous brassinosteroid levels in the vegetative and generative organs of bulbous plants showed that the amount of hormones in bulbs and shoots exceeds their content in flowers by dozens of times.